Establishment of atropisomerism in 3-indolyl furanoids: a synthetic, experimental and theoretical perspective. Issue 39 (18th July 2019) - Chatterjee, Sourav; Bhattacharjee, Pinaki; Butterfoss, Glenn L.; Achari, Anushree; Jaisankar, Parasuraman
Abstract : A number of axially chiral 3-indolyl furanoids have been synthesized and the individual enantiomers are found to be configurationally stable and isolable at room temperature. Abstract : Introduction of axial chirality in bioactive 3-indolyl furanoids has been achieved by systematic alteration of functional groups around the stereogenic axis, keeping in mind that atropisomerically pure analogues may possess different binding affinities and selectivities towards a target protein. The kinetics of racemization of axially chiral 3-indolyl furanoids have been studied through chiral HPLC analysis, electronic circular dichroism (ECD) spectroscopy, and computational modeling. The results identify the configurational parameters for optically pure 3-indolyl furanoids to exist as stable and isolable atropisomeric form.